Audiotactile temporal order judgments. - Zampini, M; Brown, T; Shore, D; Maravita, A; Röder, B; Spence, C (2005)
We report a series of three experiments in which participants made unspeeded 'Which modality came first?' temporal order judgments (TOJs) to pairs of auditory and tactile stimuli presented at varying stimulus onset asynchronies (SOAs) using the method of constant stimuli. The stimuli were presented from either the same or different locations in order to explore the potential effect of redundant spatial information on audiotactile temporal perception. In Experiment 1, the auditory and tactile stimuli had to be separated by nearly 80 ms for inexperienced participants to be able to judge their temporal order accurately (i.e., for the just noticeable difference (JND) to be achieved), no matter whether the stimuli were presented from the same or different spatial positions. More experienced psychophysical observers (Experiment 2) also failed to show any effect of relative spatial position on audiotactile TOJ performance, despite having much lower JNDs (40 ms) overall. A similar pattern of results was found in Experiment 3 when silent electrocutaneous stimulation was used rather than vibrotactile stimulation. Thus, relative spatial position seems to be a less important factor in determining performance for audiotactile TOJ than for other modality pairings (e.g., audiovisual and visuotactile).